ANALISIS PENERAPAN WHISTLEBLOWING SYSTEM TERHADAP INTERNAL FRAUD PADA PT BANK CENTRAL ASIA PERIODE TAHUN 2018-2022 - Angel, Novita; Tri Setyo Mulyono, Hendarti; Novika (Jurnal Akuntansi Bisnis Dan Keuangan, 2024)
This undergraduate thesis entitled in Bahasa Indonesia; “Analisis Penerapan Whistleblowing System Terhadap Internal Fraud Pada PT Bank Central Asia Periode Tahun 2018-2022”. This research was conducted from March 01, 2024 - April 30, 2024, has pages 90 without attachments. This study aims to determine the application of the Whistleblowing System against Internal Fraud at PT Bank Central Asia for the 2018-2022 period. The data collection techniques used are observation and documentation. The data analysis technique used is qualitative descriptive. The results showed that the mechanism for implementing the Whistleblowing System at PT Bank Central Asia in terms of the policies taken and various efforts to prevent fraud with the Whistleblowing System, the objectives and benefits of implementing the Whistleblowing System along with the flow of report processing have provided a good indication and in accordance with what is required to be applied. The effectiveness of the implementation of the Whistleblowing System in preventing internal fraud has been effective. This effectiveness can be seen from how the Whistleblowing System makes efforts to emphasize fraud figures along with actions and case resolutions taken to emphasize internal fraud cases. Keywords : Whistleblowing System, Internal Fraud.